Homology Modeling and Molecular Docking Studies of Selected Substituted Tetradecane on vlsE Borrelia spielmanii - Venu Paritala; Harsha Thummala; Talluri Naga Santosh Mohith (Journal of Molecular Docking, 2022)
VlsE is the key enzyme in antibacterial and suicide antigenic variation. While the vlsE of Borrelia burgdorferi sensu lato complex causes Lyme disease. Therefore, vlsE is considered a significant drug target for Lyme disease. In this paper, we report the model of the three-dimensional structure of vlsE resulting from a homology modeling study. Homology modeling was developed using three different software and evaluating the best model. Subsequent docking studies of the natural substrate tetradecane and known antibacterial drugs were performed with SwissDock and shed new light on the binding characteristics of the enzyme. Binding energies ranged from -2024.12 to -2032.17 kcal/mol. As a result, they might be synthesized further and developed into active commercial antibacterial drugs.